HUBUNGAN MINAT BACA DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR BAHASA INDONESIA SISWA SEKOLAH DASAR DI KOTA MAKASSAR - Mantahir, Mantahir; Hamsiah, Andi; Muhammadiah, Mas'ud (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2019)
This study aims to: (1) Knowing the relationship of reading interest with learning outcomes (2) Knowing the relationship of learning motivation with learning result Language (3) Knowing the relation of reading interest and learning motivation learning result Indonesian. Thisresearch ex postfacto which is coresional characteristic. ex postfacto research is a research that looks for un-manipulated relationship by the researcher.Population in this study are students in all Primary School in Makassar city which amounted to 100 students. Data collection techniques taken through the questionnaires. The research instrument used is questionnaire of reading interest and questionnaire of learning motivation with likert scale assessment, alternative answer consists of four options: strongly agree (SS), agree (S), disagree (TS), strongly disagree (STS). Technique of data analysis of descriptive analysis and inferential analysis.The results of this study indicate: (1) There is a significant relationship between reading interest and learning result of Indonesian language (2) There is a relationship between learning motivation and learning outcome of Indonesian language (3) There is a significant relationship between reading interest and learning motivation with learning result of Indonesian language.